Pentingnya Pendidikan Kewirausahaan pada Mahasiswa dengan Memanfaatkan Teknologi Digital Sebagai Upaya Menghadapi Revolusi 4.0 - Efa Wahyu Prastyaningtyas; Zainal Arifin (Proceedings of The ICECRS, 2019)
The 4.0 industrial revolution marked by innovation in information technology "internet of things" has a broad impact on the economy throughout the world including Indonesia. The role of higher education can be done through the implementation of entrepreneurship education by utilizing digital technology, because higher education is an agent of change that prepares students to be superior, tough, and competent in plunging into society. The purpose of writing this article provides an overview of entrepreneurship education held in universities to provide students with the provision of entrepreneurship to be ready to face the world of work by utilizing digital technology. The method used in writing this article is descriptif by using library studies so as to produce exposure in the form of theoretical ideas about the importance of entrepreneurship education to students by utilizing digital technology. The results of this study are expected to be able to equip character building entrepreneur 4.0 students, namely smart, trustworthy and creative including efforts to improve 5C aspects (creative, cognitive, collaborative, competence, cohesiveness) and able to create a generation of digitalpreneur.